Carbon dioxide flux in the drained drawdown areas of Three Gorges Reservoir - Yang, Le; Lu, Hao; Yu, Xuefang; Li, Hepeng (Frontiers in Environmental Science, 2022)
A huge amount of CO2 emissions from the drained drawdown areas of reservoirs overturns the previous result in carbon budget. Three Gorges Reservoir (TGR) has a large drawdown area, which accounts for nearly one third of the total area of the TGR. However, the total CO2 emissions from the TGR drawdown area had seldom been estimated by far. To demonstrate the contribution of CO2 emissions from the TGR drawdown areas, the study measured CO2 emissions from the downstream part of the TGR drawdown areas by the chamber method, and synthesized CO2 emissions from the other parts of TGR drawdown areas. Both the diel and seasonal variation indicated that CO2 emission fluxes were significantly higher in the drained season than in the flooded season. The average CO2 emission flux in the drained season was about 1.7 times higher than those in the inundated season in our experiments, and the ratio increased to 4.8 times when other available data was added. CO2 emission flux in the drained season was positively correlated with air temperature, soil temperature at 5 cm depth, soil water content, organic carbon, and soil nitrate nitrogen, but negatively correlated with elevations. CO2 emission from the TGR drawdown area was estimated to be 342.67–495.96 Gg yr-1 in the drained season, and offset about 80% of carbon fixation by vegetation in the TGR drawdown area. Therefore, CO2 emission from the drained soils should be included in the carbon budget of reservoir systems, especially for these reservoirs with a large drawdown area.